1999
DOI: 10.1002/(sici)1096-9861(19990510)407:3<381::aid-cne6>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal polypeptide in sacral primary sensory pathways in the cat

Abstract: Unmyelinated sensory axons in the sacral spinal cord may play a role in bladder reflexes under certain pathological conditions. Previous data suggested vasoactive intestinal polypeptide (VIP) might be contained exclusively in sensory C‐fibers, some of which innervate the bladder. This study was undertaken to describe the morphology of these VIP fibers in the sacral cord of the cat. VIP immunoreactivity was confined to unmyelinated axons observed at several levels of the sensory pathway including the dorsal roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Immunohistochemical studies of the rat conus medullaris have also demonstrated in the IML the presence of several neuropeptides, including CGRP, substance P, vasoactive intestinal peptide (VIP), neuropeptide Y, galanin, and pituitary adenylate cyclase activating polypeptide (PACAP) (Gibson et al, 1986; Wang et al, 1998; Morgan et al, 1999; Vizzard, 2001; Zvarova et al, 2004, 2005). The association between neuropeptides and dense-cored vesicles in synaptic terminals of autonomic nuclei has also been supported by electron microscopy, as immunoreactivity for VIP has been detected ultrastructurally in synaptic terminals containing a mixture of clear and dense-cored vesicles in the sacral parasympathetic nucleus of cats (Morgan et al, 1999). Additional immunohistochemical studies combined with electron microscopy are needed, however, to determine which neuropeptidergic projections may exhibit a direct synaptic connection with the PPN somata and dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies of the rat conus medullaris have also demonstrated in the IML the presence of several neuropeptides, including CGRP, substance P, vasoactive intestinal peptide (VIP), neuropeptide Y, galanin, and pituitary adenylate cyclase activating polypeptide (PACAP) (Gibson et al, 1986; Wang et al, 1998; Morgan et al, 1999; Vizzard, 2001; Zvarova et al, 2004, 2005). The association between neuropeptides and dense-cored vesicles in synaptic terminals of autonomic nuclei has also been supported by electron microscopy, as immunoreactivity for VIP has been detected ultrastructurally in synaptic terminals containing a mixture of clear and dense-cored vesicles in the sacral parasympathetic nucleus of cats (Morgan et al, 1999). Additional immunohistochemical studies combined with electron microscopy are needed, however, to determine which neuropeptidergic projections may exhibit a direct synaptic connection with the PPN somata and dendrites.…”
Section: Discussionmentioning
confidence: 99%
“…Greater basal activity in the primary bladder afferents in the DRG or in the target organ itself (i.e., urinary bladder) could result in increased pCREB expression in the absence of inflammation by increasing Ca ++ and/or cAMP in VIP −/− mice. Primary afferent cells in the DRG express VIP (Morgan et al, 1999;Hernandez et al, 2006) and VIP receptors (Yashpal et al, 1991;Braas et al, 2006). Thus, absence of VIP in the VIP −/− mice could produce a direct effect on primary afferent cells.…”
Section: Vip −/− Mice Exhibit Higher Basal Level Of P-creb-ir In Drgmentioning
confidence: 99%
“…Neuropeptides are potential mediators or modulators of inflammation and are found in human micturition pathways (Chapple et al, 1992;Lasanen et al, 1992;Smet et al, 1997;Morgan et al, 1999;Uckert et al, 2002). Changes in the expression of neuropeptides have been observed with bladder overactivity (Chapple et al, 1992;Lasanen et al, 1992;Smet et al, 1997) and in animal models of bladder inflammation (Vizzard, 2000d(Vizzard, , 2001Zvarova and Vizzard, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Neuropeptides are potential mediators or modulators of inflammation and are found in human micturition pathways (Chapple et al, 1992;Lasanen et al, 1992;Morgan et al, 1999). Changes in the expression of neuropeptides have been observed with bladder hyperreflexia (Chapple et al, 1992;Lasanen et al, 1992) and in animal models of bladder inflammation (Vizzard, 2000b(Vizzard, , 2001Zvarova and Vizzard, 2006).…”
Section: Introductionmentioning
confidence: 99%